Pengaruh Sertifikasi Halal dan Izin Edar BPOM terhadap Minat Beli Kosmetik pada Mahasiswi - Lestari, Mega; Parakkasi, Idris; Katman, Muhammad Nasri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Whether we realize it or not, in everyday life, women's needs can’t be separated from cosmetics and other beauty products to support their appearance. The increasing public interest in beauty trends encourages the cosmetic industry to develop rapidly. The desire of women to always look beautiful invites actors who are not responsible for creating or trading cosmetics that do not meet the circulation regulations. Basically, this research was conducted with the aim of knowing the effect of halal certification and BPOM distribution permit on the buying interest of female students. This study uses descriptive analysis techniques with a quantitative approach. The population in this study were students of the Faculty of Economics and Islamic Business, Alauddin State Islamic University, Makassar. In determining the sample using the formula from Krijie and Morgan with a total sample of 336 respondents. IBM Statistics SPSS 25 was used as the data analysis method in this study. From the research process, it was found that halal certification had an effect on student cosmetic buying interest. Meanwhile, the distribution permit of BPOM also influences the cosmetic buying interest of female student. Keywords : Halal certification, BPOM Circulation Permit, Buying Interest, Cosmetics.